Efeitos de um tratamento fisioterapêutico na dor, equilíbrio postural, distribuição das cargas de pressão plantar e sensibilidade de idosas diabéticas tipo 2 - Piovesan, Ana Carla (2015)
Diabetes mellitus (DM) is a metabolic disorder of multiple etiologies common in the elderly. With advancing disease, the elderly can develop pathologies that involve the entire peripheral nervous system (SNP), responsible for its damage by causing the polyneuropathy, as which as modify the quality of sensory information necessary for motor control. In this sense, it is necessary to identify risk factors and develop assessments and specific treatments. Objective: To analyze the beneficial effects of physical therapy intervention in elderly diabetic type 2 with 66.28 ± 6.21 years. There by, the dissertation was divided in two articles. Article 1: to evaluate the effects of physical therapy intervention on postural balance of diabetic type 2 elderly on two conditions of support: Romberg and Semi-Tandem. Article 2: aimed to determine the effects of a physical therapy intervention in plantar sensitivity, pain in the lower limbs and in the distribution of plantar pressure loads of elderly diabetic type 2 on two conditions of support: Romberg and Semi-Tandem. Materials and methods: for both studies, participated 21 elderly diabetic type 2 the city of Santa Maria - RS, aged 66.28 ± 6.21 years, divided into two groups: GE (experimental group); GC (control group). For selecting the groups we used the Mini- Mental State Examination (MMSE) and a physical activity questionnaire (IPAQ). To anamnesis used a questionnaire of Michigan Neuropathy Screening Instument (MNSI) and a questionnaire of self-care activities with Diabetes (QAD). The physicaltherapy intervention performed, emphasized sensory stimulation, proprioceptive, landslides, twists and myofascial work in lower limbs (LL), in order to raise adequate responses to pain improvement, sensibility, distribution of pressure loads plantar and postural balance. To obtain the results of both studies was used SPSS for Windows, held the paired t-test / Wilcoxon test and independent t / Mann- Whitney. Article 1: held assessment of postural balance through a force platform AMTI OR6- 6 2000 (Advanced Mechanical Technology, Inc.). The results were statistically significant for the plantar sensitivity (p <0.05). Article 2: evaluation of sensitivity was performed using a set of monofilaments - Semmes Weistein Monofilament Examination (SWME); evaluated the pain in the lower limbs (LL) by Visual Analogue Scale (EVA) and the evaluation of plantar pressure was performed with an barapodometry system -FootWorkPro (Arkipelago). There were significant differences in the sensitivity, pain and distribution of plantar pressure loads. It can be concluded that physical therapy intervention performed, provided stimuli and showed benefits for the elderly.